Perceiving the other in ancient Judaism and early Christianity - Bar Asher Sigal, Mikhal; Grünstäudl, Wolfgang; Thiessen, Matthew (Wissenschaftliche Untersuchungen zum Neuen Testament, 2017)
Cover -- Acknowledgements -- Table of Contents -- Albert I. Baumgarten: 1. An Ancient Debate of Disciples -- Was There an Ancient Debate of Disciples? -- Christian Supersessionism and The "Johannine" Response -- Awkward Landings -- Jesus as the Resurrected John -- cui bono -- Imagine -- Matthew Thiessen: 2. Gentiles as Impure Animals in the Writings of Early Christ Followers -- Mark -- Matthew -- Luke -- Philippians 3 -- Conclusion: Ethnic Reasoning in Ancient Judaism -- Nathan Eubank: 3. Damned Disciples: The Permeability of the Boundary between Insiders and Outsiders in Matthew and Paul -- Matthew's Gospel -- Damned Disciples in Paul -- The Inward Current -- Conclusion -- Tobias Nicklas: 4. Creating the Other: The "Jews" in the Gospel of John: Past and Future Lines of Scholarship -- The Johannine "Jews" - A Few Data and Observations -- Major Lines of Reception and Research History -- Ancient Receptions of John -- Lines of Reception after 1945 -- The Meaning of οἱ Ἰουδαῖοι in John -- The Referent of οἱ Ἰουδαῖοι in John -- The Historical Situation behind the Gospel of John -- Impulses for Future Research -- Wolfgang Grünstäudl: 5. Instant Polemics: Use and Reuse of Charges against Others in Early Christianity -- Polemics in the Epistle of Jude -- Jude in Disguise: 2 Peter -- Jude and the Carpocratians: Clement of Alexandria -- Jude and his Modern Readers -- Patricia A. Duncan: 6. The Case for Tolerance in the Early Christian (Pseudo-Clementine) Novel -- The Tripolis Discourses -- Conclusion -- Katell Berthelot: 7. The Paradoxical Similarities between the Jews and the Roman Other -- Esau/Edom: Christian Rome or Pagan Rome? -- The Similarity of the Roman Other -- An Encounter between Two Peoples -- A Rivalry of "Election" and "Vocation" between Israel and Rome -- Conflict, Military Victory and Substitution -- Conclusion.